Sucrose: A Potent Stabilizer for Carbonic Anhydrase - SARRAF, N.S.; SABOURY, A.A.; NEMATI, T.; KARBASSI, F. (Asian Journal of Chemistry, 2010)
The effect of sucrose as a very potent osmolyte and stabilizer on the structure and activity of bovine carbonic anhydrase has been studied using different techniques. Sucrose has been shown to stabilize the enzyme against inactivation alongside of time. Besides, it seems that the enzyme got greater thermal stability in the existence of sucrose because both the transition temperature (Tm) and the standard Gibbs free energy (ΔG°25) in protein thermal denaturation were increased. It seems that sucrose can have these effects through inducing some alterations in the structure of carbonic anhydrase.